Dacryocystography: From theory to current practice - Singh, Swati; Mohammad, Javed Ali; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2019)
Purpose: To provide a review and an update on dacryocystography (DCG) and its relevance in the current era. Methods: The authors performed a PubMed search of all articles published in English on DCG, digital subtraction-DCG (DS-DCG), computed tomographic DCG (CT-DCG) and magnetic resonance-DCG (MR-DCG). Data analyzed include the indications, techniques, interpretations, complication and limitations. Results: Dacryocystography has been used for illustrating the morphological and functional aspects of the lacrimal drainage system (LDS). Subtraction DCG provides the precise location of the alterations and acceptably delineates stenosis or an obstruction. Transit time for contrast into the nose varies widely across the studies. Low osmolality iodinated contrast media are tolerated well for DS-DCG and CT-DCG. However, normal saline either mixed with lidocaine or alone provided similar image quality as obtained with gadolinium for MR-DCG. CT-DCG provides useful information in complex orbitofacial trauma and lacrimal tumors. MR-DCG allows better 3D visualization of the LDS and dynamic functional evaluation. Sensitivity of CT-DCG and MR-DCG are mostly similar in identifying an LDS obstruction. Conclusion: Various forms of DCGs can provide additional information to evaluate patients with maxillo-facial trauma, functional epiphora, suspected lacrimal sac diverticula, partial nasolacrimal duct obstruction, and lacrimal drainage tumors. Canaliculi and the membranous part of the nasolacrimal duct are not yet visualized in detail and further focused studies with advanced techniques are required.
CRIS-Team Scopus Importer:2019-05-02
Keywords: CT-DCG; Dacryocystography; Epiphora; Lacrimal; MR dacryocystography; MR-DCG; Subtraction dacryocystography